If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 34X + -25 = 18 Reorder the terms: -25 + 34X = 18 Solving -25 + 34X = 18 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '25' to each side of the equation. -25 + 25 + 34X = 18 + 25 Combine like terms: -25 + 25 = 0 0 + 34X = 18 + 25 34X = 18 + 25 Combine like terms: 18 + 25 = 43 34X = 43 Divide each side by '34'. X = 1.264705882 Simplifying X = 1.264705882
| -9(x-8)+2=74 | | 2(4x+7)-5=8x+9 | | -x+3=22 | | 15t^4-2t^2+78=0 | | n/2-9=-5 | | 30=48t-16t^2 | | 3(2x+35)+5(x+1)=u | | (15+9)x(22-5)= | | u/12-8=-8 | | 44=2(3.14) | | -8(t-4)-(t+1)=4 | | 6x-4=24x+2 | | 5(x+2)+7=17 | | r/2+6=5 | | 6(2x+33)+7(x+1)=u | | 3x^2+5=21 | | 50.2=2(3.14) | | 9(x-4)+4=-32 | | 12x-2=24x+7 | | 6(2x+30)+7(x+1)=u | | 10+(a+b)= | | -0.11(13x)= | | (2*7x)+(14+2x)*15=606 | | 3(8x+31)+5(x+1)=u | | 2x+7=X+1 | | 2*7x+14+2x*15=606 | | 2x+14+2x*15=606 | | -10(x-2)= | | 6=9x-8x+3 | | -9x-6y+3= | | 18p-3+7p+31= | | (13+a)+13= |